Literature Review for the Effects of Physical Activity on Musculoskeletal Outcomes in Community-dwelling Older Adults - Kyung Choon Lim; Jeung Im Kim; Young Ran Chae (Korean Society of Women Health Nursing, 2014)
PURPOSE: The purpose of this study was to review the effects of physical activity on musculoskeletal outcomes in older Koreans. METHODS: Experimental studies were retrieved from the search engines (PubMed, CINAHL, PsycINFO, Cochrane, RISS, KISS, and KoreaMed). The selected studies for analysis were 27 articles of musculoskeletal outcomes (gait, muscle strength, flexibility, balance, grip strength, endurance, body fat, and weight) from 515 articles. RESULTS: The most common type of physical activity was a resistance exercise. There were significant improvements in gait (71.4%), muscle strength (86.7%), flexibility (63.6%), balance (72.2%), grip strength (71.4%), endurance (71.4%), body fat (57.1%), and weight (28.6%). The activity programs that apply over 150 minutes a week showed greater improvement of 69.5% than 65.0% from those did not meet the guidelines totally. CONCLUSION: Based on the review, we conclude that regular physical activity in the elderly may improve the musculoskeletal outcomes. To be more effective programs, it is necessary to meet the guidelines of 150 minutes a week or 30 minutes of moderate-intensity activities on 5 days per week for the elderly.